A ANALYSIS OF FILLERSIN THE REALITY SHOW, THE APPRENTICE - Wulan Suhendrawati, - (2009)
ABSTRACT This research is entitled Analysis of Fillers in the Reality Show 'The Apprentice'. The aim of this research is to investigate the most recurring type of fillers in the conversation of The Apprentice. The research method used in this thesis is a descriptive analysis. First, the writer identified the occurrences of fillers in conversation, and then classifies them based on Strassel's type of fillers. The result of this research shows all type of fillers do occur in the conversation of The Apprentice. The most recurring filler type is Discourse Markers (DMs). Discourse Markers in this research appears for various reasons since they used various kinds of words or phrases. In a conversation, the speaker may use more than one type of fillers.